Reforming child protection - Lonne, Bob (Routledge, 2009)
Reforming child protection : principles and themes of effective child, family and community well-being -- The chequered history of contemporary child protection practice -- Differential responses and changing social mandates -- The troubled state of organizational environments -- Service users and stakeholders -- Reforming child protection : principles and processes -- A new ethical and practice framework -- Effective organizational and service delivery models -- Planning and implementing change -- Change and the future of child and family well-being practice